2003
DOI: 10.1080/0954012031000134700
|View full text |Cite
|
Sign up to set email alerts
|

Influencing medication adherence among women with AIDS

Abstract: This study examined the effects of a ten-session cognitive-behavioural stress management/expressive supportive therapy (CBSM+) intervention on adherence to antiretroviral medication. Although the intervention was not designed to influence adherence, it was theorized that improved coping and social support could enhance adherence. Women with AIDS (N = 174) in Miami, New York and New Jersey, USA, were randomized to a group CBSM+ intervention or individual control condition. Participants were African American (55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
44
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 19 publications
0
44
0
Order By: Relevance
“…The program was subsequently adapted to include all women living with HIV and translated linguistically and culturally from English into Spanish and Creole. A healthy lifestyle program targeting multiple health risk behaviors was incorporated, and the program was found to reduce stress/ distress and depression and anxiety, decrease HIV viral load, and enhance coping and self-efficacy, while improving health status and quality of life [15][16][17][18][19][20][21][22]. Between 2007 and 2011, a translation of this evidence-Implications Practice: The Stress Management and Relaxation Training/Expressive-Supportive Therapy Women's Program (SWP) can be implemented in community-based practice, utilizing existing community health center staff with diverse education levels and training backgrounds, and achieves improved health outcomes in women living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…The program was subsequently adapted to include all women living with HIV and translated linguistically and culturally from English into Spanish and Creole. A healthy lifestyle program targeting multiple health risk behaviors was incorporated, and the program was found to reduce stress/ distress and depression and anxiety, decrease HIV viral load, and enhance coping and self-efficacy, while improving health status and quality of life [15][16][17][18][19][20][21][22]. Between 2007 and 2011, a translation of this evidence-Implications Practice: The Stress Management and Relaxation Training/Expressive-Supportive Therapy Women's Program (SWP) can be implemented in community-based practice, utilizing existing community health center staff with diverse education levels and training backgrounds, and achieves improved health outcomes in women living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Several publications from three federally funded studies conducted by UMMSM and CDN over a 10-year period confirmed the evidence base of the program [3][4][5][6][7][8][9][10][11][12][13][14][15].…”
mentioning
confidence: 86%
“…12 The scarcity of validated ART adherence questions in SSA is all the more surprising because our understanding of ART adherence in the region is largely based on patient responses to adherence questions, 19 and interventions to increase adherence in routine care are commonly evaluated using adherence questions as outcome measures. [20][21][22][23] Some studies outside of SSA have demonstrated significant associations between self-reported adherence and viral load 13 and antiretroviral (ARV) plasma concentrations. 26 However, other studies found that self-reported adherence was only weakly correlated with viral suppression and antiretroviral drug concentrations.…”
Section: Introductionmentioning
confidence: 99%